2015
DOI: 10.1097/md.0000000000001788
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Coinfections With Rhinovirus and Human Bocavirus in Hospitalized Children

Abstract: It is not clearly established if coinfections are more severe than single viral respiratory infections.The aim of the study was to study and to compare simple infections and viral coinfections of respiratory syncytial virus (RSV) in hospitalized children.From September 2005 to August 2013, a prospective study was conducted on children younger than 14 years of age, admitted with respiratory infection to the Pediatric Department of the Severo Ochoa Hospital, in Spain. Specimens of nasopharyngeal aspirate were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 31 publications
12
60
1
7
Order By: Relevance
“…When we analyzed data for emerging and less frequently studied viruses, we detected hBoV more frequently as a co‐infection than as single infection (55.9% vs 44.1%), followed by hMPV (40.0%) (Figure B), in agreement with previous studies . In the earlier study conducted in Taiwan, Chen et al reported multiple viral infection in 72.7% of children with hBoV and in 63.2% of those hMPV.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When we analyzed data for emerging and less frequently studied viruses, we detected hBoV more frequently as a co‐infection than as single infection (55.9% vs 44.1%), followed by hMPV (40.0%) (Figure B), in agreement with previous studies . In the earlier study conducted in Taiwan, Chen et al reported multiple viral infection in 72.7% of children with hBoV and in 63.2% of those hMPV.…”
Section: Discussionsupporting
confidence: 89%
“…In the earlier study conducted in Taiwan, Chen et al reported multiple viral infection in 72.7% of children with hBoV and in 63.2% of those hMPV. The role of multiple viral detection remains poorly understood, given that RT‐PCR can sometimes detect a viral respiratory infection even in asymptomatic children . RSV and hMPV are all rare in asymptomatic children, in contrast, PCR frequently detects hCoV and hBoV in healthy controls, suggesting that caution is needed when inferring a causal relationship between viral detection and respiratory diseases, even in symptomatic patients, and could even reflect virus left over from a previous infection.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have evaluated the presence of mixed viral infections at the clinical setting for adult populations. Significant rates of mixed infections have been reported in several studies mainly involving pediatric populations while very little data exist regarding adult patients . The clinical significance of mixed viral infections is a matter of debate with some data supporting a role for increased illness severity and adverse outcomes including hospitalizations and some not .…”
Section: Introductionmentioning
confidence: 99%
“…Co-detection with other viral pathogens is common in HBoV-positive patients as shown in previous studies 20,21 . In our study we did not investigate any other potential pathogens for this reason, it is difficult to say that all the symptoms are associated with only HBoV positivity.…”
Section: Discussionmentioning
confidence: 92%